Kekuatan Musik dalam Pendidikan Karakter Manusia - Panjaitan, Adi Putra (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
Generally, listening to music is a fun activity to almost everyone. Furthermore, music can be used as an entertainment and a means of expressing the self. Music can be found everywhere easily, whether in private or in public places, and it has become part of human life. In this article, the author explores the power of music through its particular elements in relation to human character education. In other words, music is considered to have influences in shaping the character of the self, albeit in daily experiences music is often seen as merely entertainment. The elements of music, which includes melody, rhythm, harmony, beat, dynamics, timbre, and lyrics, are correlated to the effects each may bring towards the listeners. In this approach, music is considered to have a transformative role in shaping and orienting the character of the listener, since the person is not merely focused on the thinking mind, but to the sensitivity of the self perceiving the sound of music.